2016
DOI: 10.1590/s0102-865020160110000008
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular loss after arteriovenous and arterial clamping for renal warm ischemia in a swine model

Abstract: PURPOSE:To evaluate the glomerular loss after arteriovenous or arterial warm ischemia in a swine model. METHODS:Twenty four pigs were divided into Group Sham (submitted to all surgical steps except the renal ischemia), Group AV (submitted to 30 minutes of warm ischemia by arteriovenous clamping of left kidney vessels), and Group A (submitted to 30 minutes of ischemia by arterial clamping). Right kidneys were used as controls. Weigh, volume, cortical volume, glomerular volumetric density (Vv[Glom]), volume-weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The results indicated that the volumes of the renal tubules were augmented, which is in accordance with the literature [21]. Unbiased stereology has been used for studying the number of glomeruli in different conditions [12, 14, 16, 39] and is considered a highly sensitive method [40]. Thus, it may be thought that the obstructed kidney did not promote alterations in the number of glomeruli but in the tubular structure of contralateral kidney.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results indicated that the volumes of the renal tubules were augmented, which is in accordance with the literature [21]. Unbiased stereology has been used for studying the number of glomeruli in different conditions [12, 14, 16, 39] and is considered a highly sensitive method [40]. Thus, it may be thought that the obstructed kidney did not promote alterations in the number of glomeruli but in the tubular structure of contralateral kidney.…”
Section: Discussionsupporting
confidence: 85%
“…Analyses of Vv(glom) and VWGV were performed using the ImageJ software version 1.46r (NIH, Bethesda, MD, USA). An estimation of the total number of glomeruli per kidney was calculated by multiplying the CV by the Vv(glom) and dividing the result by the VWGV [14, 16]. …”
Section: Methodsmentioning
confidence: 99%
“…General anesthesia was induced with propofol (3mg/kg, IV) and maintained with isoflurane (2% in oxygen, given by an endotracheal tube). Under general anesthesia and by using aseptic technique, the surgical procedure involved transperitoneal laparoscopic access, as previously used in pigs 15,16 . The left kidney was completely exposed by dissection.…”
Section: ■ Methodsmentioning
confidence: 99%
“…The volume weighted mean glomerular volume (VWGV), was estimated by using the point-sampled intercepts method 14,16,18,22,23 , analyzing 50 glomeruli per kidney.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this regard, an objective assessment of the glomeruli may accurately identify the functional units that were damaged during WI. Stereological methods such as those used in our study reduce sampling bias and may increase accuracy in identifying irreversible kidney damage after ischemic injury [14,18,20] .…”
Section: Discussionmentioning
confidence: 99%